Jordan Derivations on Completely Semiprime GammaRings - Rahman, Md Mizanor; Paul, Akhil Chandra (GANIT: Journal of Bangladesh Mathematical Society, 2016)
In this paper we prove that under a suitable condition every Jordan derivation on a 2-torsion free completely semiprime ?-ring is a derivation. GANIT J. Bangladesh Math. Soc.Vol. 34 (2014) 21-26